The Issues of Professional Communication (Report on the International Scientific and Practical Conference INTERLINGUA-2021) - M. S. Matytsina (Дискурс профессиональной коммуникации, 2021)
The paper deals with the results of the International Scientific and Practical Conference INTERLINGUA-2021, held on May 18-19, 2021 at Lipetsk State Technical University. Within the framework of the conference, the issues of the professional training of highly qualified specialists in the information-digital space were discussed. The conference participants focused their attention on the important role of professional communication as a component of communicative competence. It was noted that professional communication plays a pivotal role in the educational system of the university, since a specialist who does not have the skills to conduct a constructive dialogue, does not know how to establish contact with the interlocutor, to study his/her point of view, does not grow professionally, is not accepted by the society, and therefore becomes uncompetitive. The reports of the conference participants were distinguished by the undoubted depth of theoretical analysis and high practical relevance of the problems under consideration. As a result of the conference, round tables were held, at which the most significant aspects of professional communication, its reflection in the linguistic consciousness were discussed. The participants and guests of the conference, noting its usefulness, recognized the need to make it an annual event.